'Ouvrez l'histoire'. Revolutionaire geschiedenispolitiek in de Zuidelijke Nederlanden (1792-1799) - Brecht Deseure (BMGN: Low Countries Historical Review, 2010)
‘Ouvrez l’histoire’. Revolutionary Historical Politics in the Southern Netherlands (1792-1799) Based on speeches given by revolutionary administrators in Antwerp and Brussels during the French period, this article investigates the uses of the past in official revolutionary discourse. The revolutionary conception of liberty – based on a break with the past and a return to mankind’s original state of natural freedom – was diametrically opposed to the historically grounded Brabantine understanding of liberty. Yet in practice, elements of the native historical culture were subtly integrated into the official discourse. At a national level, the cherished myth of the Belgians as defenders of freedom was invoked to enhance the revolutionary claim. At the local level, parallels were even drawn between the revolutionary intervention and specific episodes of local urban history, thus making the revolutionary message more recognizable for the population. These findings provide greater nuance to the existing picture of the French discourse as firmly anti-historical and unadjusted to local circumstances.